Intensify chemical reduction to remove nitrate from groundwater via internal microelectrolysis existing in nano-zero valent iron/granular activated carbon composite. Issue 30 (26th June 2016) - Hu, Sihai; Zhang, Chengjun; Yao, Hairui; Lu, Cong; Wu, Yaoguo
Abstract: A composite combination of nano-zero valent iron (nZVI) and granular activated carbon (GAC) was introduced to achieve nitrate transformation into nitrogen with minimum byproducts via chemical reduction. The results showed that nitrate removal was significantly intensified and GAC was an excellent partner of nZVI chemical reduction. Both the dispersion and long-term reactivity of nZVI were improved, and more than 80% of nitrate was removed at 10 g/L nZVI/GAC composite within 90 min in steady state. The byproducts of nitrite and ammonium formed in reduction process were below 0.008 and 0.04 mg/L, respectively, and nitrogen was the main end product, which was confirmed by X-ray photoelectron spectroscopy analysis. Moreover, the kinetic model of nitrate reduction by nZVI/GAC composite can be described well by pseudo-first-order reaction kinetic ( R 2 = 0.984). The intensification is closely related to the dispersion effect of GAC matrix to nZVI and the promotion effect to electrons transfer between nZVI and nitrate pollutant of internal iron–carbon microelectrolysis existing in such a composite. Therefore, the findings are very beneficial to develop an efficient and low-cost chemical remediation method for nitrate-contaminated groundwater.